2011
DOI: 10.1089/cyber.2010.0267
|View full text |Cite
|
Sign up to set email alerts
|

The Closer the Relationship, the More the Interaction on Facebook? Investigating the Case of Taiwan Users

Abstract: This study argues for the necessity of applying offline contexts to social networking site research and the importance of distinguishing the relationship types of users' counterparts when studying Facebook users' behaviors. In an attempt to examine the relationship among users' behaviors, their counterparts' relationship types, and the users' perceived acquaintanceships after using Facebook, this study first investigated users' frequently used tools when interacting with different types of friends. Users tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…Previous studies indicated that adolescents make new friends from strangers (Lenhart & Madden, 2007a;Wolak et al, 2002) using Facebook games (Hsu et al, 2011). A survey by Lenhart and Madden (2007b) suggested that 32% of online teens were contacted by strangers, of which 23% reported feeling scared or uncomfortable because of that contact.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, only some Facebook users build online relationships with new friends. According to a Taiwanese study by Hsu, Wang and Tai (2011), adolescents typically interact with new friends mainly through games. Similar findings were obtained by Vasalou, Joinson, and Courvoisier (2010), who investigated the practices of 423 Facebook users from five countries, and found that Facebook games and applications were useful for meeting new friends and joining a group.…”
Section: Facebook Friends In Different Close Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations